Locality and Word Order in Active Dependency Formation in Bangla - Chacón, Dustin A.; Imtiaz, Mashrur; Dasgupta, Shirsho; Murshed, Sikder M.; Dan, Mina; Phillips, Colin (Frontiers in Psychology, 2016)
Research on filler-gap dependencies has revealed that there are constraints on possible gap sites, and that real-time sentence processing is sensitive to these constraints. This work has shown that comprehenders have preferences for potential gap sites, and immediately detect when these preferences are not met. However, neither the mechanisms that select preferred gap sites nor the mechanisms used to detect whether these preferences are met are well understood. In this paper, we report on three experiments in Bangla, a language in which gaps may occur in either a preverbal embedded clause or a postverbal embedded clause. This word order variation allows us to manipulate whether the first gap linearly available is contained in the same clause as the filler, which allows us to dissociate structural locality from linear locality. In Experiment 1, an untimed ambiguity resolution task, we found a global bias to resolve a filler-gap dependency with the first gap linearly available, regardless of structural hierarchy. In Experiments 2 and 3, which use the filled-gap paradigm, we found sensitivity to disruption only when the blocked gap site is both structurally and linearly local, i.e., the filler and the gap site are contained in the same clause. This suggests that comprehenders may not show sensitivity to the disruption of all preferred gap resolutions.